2013
DOI: 10.3389/fnhum.2013.00591
|View full text |Cite
|
Sign up to set email alerts
|

Oblique effect in visual mismatch negativity

Abstract: We investigated whether visual orientation anisotropies (known as oblique effect) exist in non-attended visual changes using event-related potentials (ERP). We recorded visual mismatch negativity (vMMN) which signals violation of sequential regularities. In the visual periphery unattended, task-irrelevant Gábor patches were displayed in an oddball sequence while subjects performed a tracking task in the central field. A moderate change (50°) in the orientation of stimuli revealed no consistent change-related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 70 publications
1
32
1
Order By: Relevance
“…To explore whether deficits are present in the processing of elementary visual features here we used rare changes in orientation of Gabor patches to elicit MMN. Prior studies reported reliable vMMN response to orientation deviants (Astikainen et al, 2004;Kimura et al, 2009;Czigler and Sulykos, 2010;Takacs et al, 2013) in healthy subjects, therefore we used a simple oddball paradigm where we varied the probabilities of Gabor patches with different orientations. Our hypothesis was that the mismatch response to rare orientation changes will be reduced in the patients compared to controls.…”
Section: Previous Results In Mmn Research-hypothesesmentioning
confidence: 99%
“…To explore whether deficits are present in the processing of elementary visual features here we used rare changes in orientation of Gabor patches to elicit MMN. Prior studies reported reliable vMMN response to orientation deviants (Astikainen et al, 2004;Kimura et al, 2009;Czigler and Sulykos, 2010;Takacs et al, 2013) in healthy subjects, therefore we used a simple oddball paradigm where we varied the probabilities of Gabor patches with different orientations. Our hypothesis was that the mismatch response to rare orientation changes will be reduced in the patients compared to controls.…”
Section: Previous Results In Mmn Research-hypothesesmentioning
confidence: 99%
“…Takács et al, 2013), i.e., the possibility that the sensitivity to oblique lines in forward and backward directions (/ and \) is different. This possibility has some support from the larger N1 to the N stimuli over the right posterior locations.…”
Section: =0=0=0=0=0=0=0=0=0=0=0=0=0=0=0=0=0=0=mentioning
confidence: 99%
“…www.frontiersin.org January 2015 | Volume 8 | Article 1074 | 2 Takács et al (2013) investigated electrophysiological correlates of the oblique effect under unattended and attended conditions using an oddball design. The oblique effect refers to that the perceptual system is more sensitive to cardinal (vertical and horizontal) than oblique line orientations.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%